Distributed Algorithms for a Replication Problem of Popular Network Data - Jiang, Xiaofeng; Li, Jun; Xi, Hongsheng (Journal of network and systems management, 2016)
The replication of popular data objects can effectively reduce the access time and bandwidth requirements of network services. We study the replication problem in the model of distributed replication groups and propose two distributed algorithms: an approximation optimal replication algorithm, which is an asynchronous distributed algorithm as it takes more time to be completed. However its performance approaches the optimal algorithm, and a fast replication algorithm that is very suitable as the initial algorithm of the approximation optimal algorithm. We give a proof of the complexity of the algorithms, and show that the time and communication complexities of the algorithms are polynomial with respect to the number of objects and the maximum storage capacities of the servers. Finally, simulation experiments are performed to investigate the performance of the algorithms, and the results show that the two algorithms can effectively solve the replication problem.